الزراعة ودورها التنموي في ضوء القرآن الكريم : دراسة موضوعية تحليلية - حاج مأمينج، هشام (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
This study addresses agriculture and its developmental role in the light of the Qur'an. As an objective analytical study, the researcher applied the inductive approach to collect verses of the Qur'an related to agriculture, and peruse the statements and views of scholars on the subject. The analytical approach was used to analyze Qur'anic texts related to the subject of the study in order to highlight the extent to which the Qur'an gives attention to agriculture, and to reveal its role in the development of various aspects of human life, such as food, economics, environment and public health. In the field of food development, the study found that the Qur'an focuses on agriculture as a major source in the development and diversity of food resources, an important factor in achieving food security, and to make society stable and secure. In the field of economic development, the study reveales that agriculture plays an important role in attaining economic development by providing employment opportunities to the community. This increases their revenue, and develops taxes proceeds that address the problem of poverty and some types of unemployment. It also reveales that agriculture is the fundamental basis in the development of industry and commerce, and in the generation of state income. In the field of environmental development, the study shows that the Qur'an is concerned with the protection and conservation of trees, and warned against cutting and destroying them. It considers those who damage trees to be among the corruptors of the earth, since trees and plants play a role in reforming, improving and developing the environment, in addition to their importance in making the surroundings beautiful and evoking feelings of joy and pleasure among people. As for the field of health development, the study concludes that most herbs and fruits mentioned in the Qur'an are the type of plants grown in gardens and orchards, and are obtained by human efforts in cultivation. These herbs and fruits have great nutritional and medical benefits, thereby they contribute to the healthy development of the human being.